Intergenerational transmission of parental risky health behaviors in Chinese children: Are there socioeconomic status differences? - Yu, Zexuan; Qin, Wen; Li, Jiajia (Frontiers in Medicine, 2023)
Background: Risky health behaviors in childhood, including smoking, drinking alcohol, and poor diet, are major sources of non-communicable diseases in adulthood. This study was intended to examine how parents affect children’s risky health behaviors, and whether intergenerational transmission differed by Socioeconomic Status (SES). Methods: Data were extracted from the 1991-2015 China Health and Nutrition Survey (CHNS). Smoking (n=5946), alcohol drinking (n=7821), and sugar-sweetened beverages (SSBs) drinking (n=3537) were singled out as proxies for risky health behaviors in children. A binary choice model for panel data with random effect specification was employed to examine whether the risky health behaviors can be transmitted from parents to their children. Subsequently, we conducted a seemingly unrelated test to explore the difference in parental transmission between SES groups. Results: We found strong intergenerational persistence of smoking, alcohol drinking, and SSBs drinking behaviors, except mothers’ smoking behavior. Mothers had a greater influence on children’s alcohol drinking and SSBs drinking behaviors than fathers, both in urban and rural areas, and in different SES groups. The intergenerational transmission of SSBs drinking behaviors exhibited a downward SES gradient for both urban and rural families. In urban areas, mothers’ drinking behavior has a downward gradient with their education level, occupation, and income, but in rural areas, the influence of mothers' drinking behavior is in the same direction with the upward gradient of education level and occupation type. In rural areas, the influence of fathers’ drinking and smoking behaviors appears to show a mainly positive gradient with SES, while some become a downward gradient among urban fathers. Conclusions: Parents’ behaviors and socioeconomic status could make sense in the initiation of their offspring’s risky health behaviors. To promote healthy behaviors, policymakers can introduce health education programs for parents, especially for rural areas and low SES parents.